Black Africa the economic and cultural basis for a federated state - Diop, Cheikh Anta. (Westport, Conn Africa World Press, 1987)
This expanded edition continues Diop's campaign for the political and economic unification of the nations of black Africa. It concludes with a lengthy interview with Diop.
Translation of: Les fondements économiques et culturels d?un état fédéral d?Afrique noire.
Keywords: Pan-Africanism.